2004
DOI: 10.1084/jem.20031272
|View full text |Cite
|
Sign up to set email alerts
|

A Defect in Nucleosome Remodeling Prevents IL-12(p35) Gene Transcription in Neonatal Dendritic Cells

Abstract: To gain insight into the inability of newborns to mount efficient Th1 responses, we analyzed the molecular basis of defective IL-12(p35) expression in human neonatal monocyte-derived dendritic cells (DCs). Determination of IL-12(p35) pre-mRNA levels by real-time RT-PCR revealed that transcriptional activation of the gene in lipopolysaccharide-stimulated neonatal DCs was strongly impaired compared with adult DCs. We next showed that p50/p65 and p65/p65 dimers interact with kB#1 site, a critical cis-acting eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 15 publications
(25 reference statements)
5
132
0
2
Order By: Relevance
“…Reduced IL-12p70 synthesis in cord blood moDCs has been associated with impaired chromatin remodeling in the IL-12p35 promotor region, suggesting epigenetic regulation of gene transcription (Goriely et al, 2004). Here we identified an additional extrinsic cause for IL-12p35 deficiency in neonatal DCs.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 71%
“…Reduced IL-12p70 synthesis in cord blood moDCs has been associated with impaired chromatin remodeling in the IL-12p35 promotor region, suggesting epigenetic regulation of gene transcription (Goriely et al, 2004). Here we identified an additional extrinsic cause for IL-12p35 deficiency in neonatal DCs.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 71%
“…We previously demonstrated that neonatal DC present a defect in IL-12(p35) expression. This deficient IL-12(p35) gene expression is associated with specific epigenetic phenomenons, involving impaired nucleosome remodeling [12]. More recently, we observed that interferon regulatory factor (IRF)-3 is essential for TLR-4-induced IL-12(p35) synthesis and that human newborns present a decreased activation of this transcription factor (V. Albarani et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 96%
“…Assessment of NF-jB, or IRF3 binding activities in nuclear extracts by Trans-AM p65/RelA, p50, c-Rel or IRF3 transcription factor assay kits (Active Motif Europe, Rixensart, Belgium) was described earlier [47]. Briefly, 5 lg nuclear extract from each sample was incubated in plate-coated with consensus NF-jB or ISRE oligonucleotides.…”
Section: Rna Purification and Real-time Quantitative Pcrmentioning
confidence: 99%